Early administration of amino acids with different doses in low birth weight premature infants - Li, Yue (J Res Med Sci, 2020)
BACKGROUND: The reasonable use of amino acids (AAs) in parenteral nutrition (PN) is very critical to the growth and development of premature infants. However, the appropriate dose of AAs has not been determined. Our study was designed to investigate the clinical effect of two different doses of AAs in PN for low birth weight premature infants. MATERIALS AND METHODS: This randomized controlled study included 191 preterm infants who admitted to the neonatal intensive care unit of the First Affiliated Hospital of Nanjing Medical University from June 2015 to December 2016 and they were randomly divided into Group 1 (n = 81) and Group 2 (n = 110). In Group 1, the starting dose of AAs dose was 1.0–1.5 g/kg/day, which was increased by 0.5 g/kg with the maximum dose at 3.5 g/kg/day. In Group 2, the starting dose of AAs was 1.8–2.5 g/kg/day and was increased by 1.0 g/kg with the maximum dose at 4.0–4.5 g/kg/day. We analyzed the clinical characteristics, body weight, body length, total calorie intake, nonprotein calorie intake, total protein intake, liver and kidney function, and complications of the two groups of preterm infants. RESULTS: The start of enteral feeding and the recovery of birth weight in Group 2 were earlier than those in Group 1 (3.83 ± 3.15 day vs. 5.53 ± 5.63 day, P = 0.016 and 6.36 ± 4.88 day vs. 8.48 ± 9.27 day, P = 0.043, respectively). The duration of PN and the time before total enteral nutrition were shorter in Group 2 than in Group 1 (16.46 ± 10.33 day vs. 21.41 ± 18.00 day, P = 0.029 and 15.47 ± 10.54 day vs. 19.47 ± 14.57 day, P = 0.038; respectively). The duration of mechanical ventilation (1.12 ± 2.62 day vs. 3.31 ± 8.13 day, P = 0.028) in Group 2 was shorter than that in Group 1. CONCLUSION: High doses of AAs in the early PN for preterm infants facilitate the promotion of early growth and development, advance recovery of birth weight, reduce the duration of PN, and reduce respiratory support without increasing the incidence of complications.